Rekontekstualisasi Hadis Dalam Dakwah Digital: Studi Kasus Akun Tiktok Kadam Sidik - Zulfirman Manik; Khofifah Ayuningtias; Afrida Yanti Lubis; Aswindi Tanjung; Kaila Nadia (Tabayyun : Journal Of Islamic Studies, 2025)
This study aims to examine how hadiths are recontextualized within digital da'wah practices, focusing on the TikTok account of Kadam Sidik as a case study. The research explores the transformation of classical Islamic messages into contemporary digital narratives tailored for short-form video platforms. Using a qualitative content analysis method, the study analyzed selected TikTok videos that explicitly reference or interpret hadiths, examining their thematic focus, visual presentation, and engagement strategies. The findings reveal that Kadam Sidik employs a contextual and conversational approach, adapting hadith content to resonate with younger, digitally-native audiences. His videos often simplify complex theological messages using local idioms, storytelling, humor, and culturally relevant analogies, thus enabling broader accessibility and emotional connection. Furthermore, the integration of hadith into popular TikTok formats, such as duets, reactions, and trending audio, illustrates a dynamic form of religious communication that blends tradition with modernity. The study concludes that the recontextualization of hadith in digital da'wah not only revitalizes classical Islamic teachings but also signifies a broader shift in religious authority and pedagogy within the social media landscape. These findings suggest the need for further scholarly attention to how digital platforms are reshaping the ways sacred texts are interpreted, transmitted, and received in the contemporary Muslim world.